Improved Detection of Candida spp. fks Hot Spot Mutants by Using the Method of the CLSI M27-A3 Document with the Addition of Bovine Serum Albumin - Garcia, Guillermo Manuel (2011)
Echinocandins are highly bound to serum proteins, altering their antifungal properties. The addition of 50% human serum to the MIC assay improves the identification of echinocandin-resistant Candida spp. harboring fks hot spot mutations. However, this modification cannot readily be applied to the method of the CLSI M27-A3 document due to safety and standardization difficulties. The aim of this study was to evaluate commercial bovine serum albumin (BSA) as a safe and standardized alternative to human serum. A collection of 28 echinocandin-susceptible strains, 10 Candida parapsilosis sensu lato strains (with naturally reduced echinocandin susceptibility), and 40 FKS hot spot mutants was used in this work. When RPMI 1640 was used for susceptibility testing, wild-type strains and fks mutants showed MIC range overlaps ( 2, 1, and 3 2-fold-dilution steps separated these populations for anidulafungin, caspofungin, and micafungin, respectively). On the other hand, the addition of BSA to RPMI 1640 differentially increased echinocandin MIC values for these groups of strains, allowing better separation between populations, with no MIC range overlaps for any of the echinocandin drugs tested. Moreover, the use of RPMI-BSA reduced the number of fks hot spot mutant isolates for which MIC values were less than or equal to the upper limit for the wild type (very major errors) from 9, 2, and 7 with RPMI alone to 3, 0, and 3 for anidulafungin, caspofungin, and micafungin, respectively. When RPMI-BSA was used to study the susceptibility of C. parapsilosis sensu lato species to echinocandins, the strains behaved as anidulafungin- and micafungin-resistant isolates (MIC, >8 g/ml). These data support the need for a revision of the CLSI protocol for in vitro testing of echinocandin susceptibility in order to identify all or most of the fks hot spot mutants. Also, caspofungin could be used as a surrogate marker of reduced susceptibility to echinocandins.